Modelo SWAT2005 aplicado às sub-bacias dos rios Conrado e Pinheiro Pato Branco-PR - Baltokoski, Valmir (2008)
Hydrological models developing that may to predict the nonpoint source pollution and the land use and occupation impacts on water quality has been a powerful tool at agricultural systems study. Within this context, the objective of the present research work was to evaluate the SWAT 2005 (Soil and Water Assessment Tool) applicability to simulate surface runoff, sediments yield and total phosphorous flow mass. The research was developed in two contiguous watersheds, from Conrado and Pinheiro rivers, on the Pato Branco River basin, from Pato Branco and Mariopolis counties, Parana State. Climatological data relative to period 1979/2006 and observed data of flow rate, sediments yeld and total phosphorous concentration relative to 2004/2005 years, taken at two monitoring locations, were used. The model requires input data in spatial format concerning to land use and soils data, associated to a digital elevation model (DEM). It was used the AvSWAT_X interface with ArcView 3.3® and its extension Spatial Analyst 2.0®, for input and manipulation data. Monthly and yearly averages of flow rate, sediments yeld and total phosphorous mass flow were compared to the observed values, being this proceeding used in the model calibration and evaluation. The Nash-Sutcliffe Coefficient (COE) and the Sum of Deviations of the Simulated Data (Dv) were used to evaluate the modeling efficiency. The results have proved to be satisfactory for the several modelings.